Identification of fibroblast growth factor 15 as a novel mediator of liver regeneration and its application in the prevention of post-resection liver failure in mice. Issue 6 (3rd January 2013) - Uriarte, Iker; Fernandez-Barrena, Maite G; Monte, Maria J; Latasa, Maria U; Chang, Haisul C Y; Carotti, Simone; Vespasiani-Gentilucci, Umberto; Morini, Sergio; Vicente, Eva; Concepcion, Axel R; Medina, Juan F; Marin, José Juan G; et al.
Abstract : Objective: Cholestasis is associated with increased liver injury and morbidity after partial hepatectomy (PH), yet bile acids (BAs) are emerging as important mediators of liver regeneration. Fibroblast growth factor 15 (Fgf15, human FGF19) is a BA-induced ileum-derived enterokine that governs BA metabolism. We evaluated the relevance of Fgf15 in the preservation of BA homeostasis after PH and its potential role in the regenerative process. Design: Liver regeneration after PH was studied in Fgf15 −/− and Fgf15 +/+ mice. The effects of the BA sequestrant cholestyramine and adenovirally delivered Fgf15 were examined in this model. The role of Fgf15 in BA-induced liver growth was tested in Fgf15 −/− mice upon cholic acid (CA) feeding. The direct mitogenic effect of Fgf15 was evaluated in cultured mouse hepatocytes and cholangiocytes. Results: Fgf15 −/− mice showed marked liver injury and mortality after PH accompanied by persistently elevated intrahepatic BA levels. Cholestyramine feeding and adenovirally delivered Fgf15 reduced BA levels and significantly prevented this lethal outcome. Fgf15 also reduced mortality after extensive hepatectomy in Fgf15 +/+ animals. Liver growth elicited by CA feeding was significantly diminished in Fgf15 −/− mice. Proliferation of hepatocytes and cholangiocytes was also noticeably reduced in CA-fed Fgf15 −/− mice. Fgf15 induced intracellular signalling and proliferation of cultured hepatocytes and cholangiocytes. Conclusions: Fgf15 is necessary to maintain BA homeostasis and prevent liver injury during liver regeneration. Moreover, Fgf15 is an essential mediator of the liver growth-promoting effects of BA. Preoperative administration of this enterokine to patients undergoing liver resection might be useful to reduce damage and foster regeneration.